Predictive Value of Netrin-1 Expression and Ultrasonic Blood Flow in Cervical Intraepithelial Neoplasia Severity - Liu B; Wei L; Wu L; Wang H; Wang H; Yu Q (International Journal of Women's Health)
Bo Liu, Ling Wei, Lirui Wu, Huiying Wang, Hongli Wang, Qian Yu Department of Gynecology, Hebei Petro China Center Hospital, Langfang, People’s Republic of ChinaCorrespondence: Ling Wei, Email 74037604@qq.comObjective: To analyze the relationship and predictive value of Netrin-1 expression and ultrasonic blood flow parameters with the severity of cervical intraepithelial neoplasia (CIN).Methods: A retrospective analysis was performed on 115 patients diagnosed with CIN and 37 patients with chronic cervicitis, all of whom underwent surgical intervention. The expression levels of Netrin-1 were evaluated through immunohistochemical staining and quantitative fluorescence PCR. Doppler ultrasound was employed to quantify flow index (FI), vascularization index (VI), and vascularization flow index (VFI) using VOCAL software. Statistical analyses, including correlation analysis, logistic regression, and receiver operating characteristic (ROC) curve analysis, were conducted to assess the predictive value of Netrin-1 expression and ultrasound-derived blood flow parameters.Results: FI, VI, and VFI increased with CIN grade, showing significant differences between CIN II, CIN III, and the control group (P < 0.05). Netrin-1 levels were negatively correlated with FI, VI, and VFI (correlation coefficients of − 0.287, − 0.309, and − 0.298; P < 0.05). Logistic regression indicated that Netrin-1 positivity was a protective factor against CIN III, while FI, VI, and VFI were risk factors. The AUC for Netrin-1 was 0.712, with sensitivity and specificity of 76.4% and 79.5% (P < 0.05).Conclusion: Netrin-1 expression is significantly reduced in CIN patients, whereas Doppler ultrasound-derived blood flow parameters—FI, VI, and VFI—are markedly elevated. Both Netrin-1 levels and these ultrasound parameters exhibit a strong correlation with the severity of cervical lesions. Notably, Netrin-1 is negatively correlated with FI, VI, and VFI. Furthermore, Netrin-1 positivity serves as a protective factor against CIN III lesions, while elevated levels of FI, VI, and VFI are associated with increased risk for these lesions. The expression levels of both Netrin-1 and ultrasound parameters provide valuable predictive insights for the early screening, diagnosis, and prevention of cervical cancer.Keywords: Netrin-1, ultrasonic blood flow parameters, cervical intraepithelial neoplasia, severity, predictive value